2013
DOI: 10.3171/2012.11.focus12373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of previous botulinum neurotoxin treatment on microvascular decompression for hemifacial spasm

Abstract: Object The objective of this study was to investigate the clinical characteristics, intraoperative findings, complications, and outcomes after the first microvascular decompression (MVD) in patients with and without previous botulinum neurotoxin treatment for hemifacial spasm (HFS). Methods The authors analyzed 246 MVDs performed at the University of Pittsburgh Medical Center between January 1, 2000, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…We report that the LSR was abolished in 61.5% of cases, which is consistent with the report of patients with prior Botox treatment. 40 The fully endoscopic approach is limited in that the scope itself is prone to blood soiling and requires irrigation or antifogging. The scope also lacks 3D information feedback.…”
Section: Discussionmentioning
confidence: 99%
“…We report that the LSR was abolished in 61.5% of cases, which is consistent with the report of patients with prior Botox treatment. 40 The fully endoscopic approach is limited in that the scope itself is prone to blood soiling and requires irrigation or antifogging. The scope also lacks 3D information feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Regular toxin injection can be extended to 20 years, but each treatment relieves symptoms for only several months. Therefore, MVD remains the definitive treatment, especially for patients previously treated with botulinum toxin [22]. However, several studies have reported symptom recurrence and serious complications (such as hearing loss and facial nerve palsy) after MVD [23].…”
Section: Discussionmentioning
confidence: 99%
“…The effects persisted for at least 7 months, with low to negligible recurrence rates [13]. The clinical results were substantiated with corresponding decreases in cutaneous blood flow, as measured using laser Doppler flowmetry [14]. Botulinum toxin works as a neuromodulator at the neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%